2011
DOI: 10.1002/oa.1238
|View full text |Cite
|
Sign up to set email alerts
|

Following the white rabbit: A case of a small game procurement site in the upper palaeolithic (Sala de las Chimeneas, Maltravieso Cave, Spain)

Abstract: The role of small game in Upper Palaeolithic economies has been examined by several authors over the past few decades. Among the small fauna, rabbits seem to have been a widely exploited resource in certain geographic areas, making them one of the main sources for subsistence in hunter-gatherer groups of southwestern Europe. Examining aspects such as anatomic profiles, demographics and taphonomic modifications (including bone breakage) allows us to approach determining the origins of the accumulation of assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…In addition, rabbit accumulations could be intrusive because of natural death in their burrows. In fact, taphonomic studies of archaeological assemblages have shown that they are often the product of combinations of anthropogenic and/or not anthropogenic agents (Hockett and Haws, ; Pérez Ripoll, ; Sanchis Serra and Fernández Peris, ; Rodríguez‐Hidalgo et al ., ; Lloveras et al ., , ). Therefore, to understand human subsistence activities in the past it is essential to establish how a given faunal assemblage accumulated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rabbit accumulations could be intrusive because of natural death in their burrows. In fact, taphonomic studies of archaeological assemblages have shown that they are often the product of combinations of anthropogenic and/or not anthropogenic agents (Hockett and Haws, ; Pérez Ripoll, ; Sanchis Serra and Fernández Peris, ; Rodríguez‐Hidalgo et al ., ; Lloveras et al ., , ). Therefore, to understand human subsistence activities in the past it is essential to establish how a given faunal assemblage accumulated.…”
Section: Introductionmentioning
confidence: 99%
“…The cave consists of several rooms and corridors developed as a karst system partially filled with allochthonous sediments (Jord a Pardo, 1988). The site is known mainly due to an important group of Paleolithic rock art (Ripoll L opez, 1999) although the research developed in recent decades indicate a prolonged anthropic use of the cavity that can be traced back to the late Middle Pleistocene (Canals et al, 2010;Rodríguez Hidalgo et al, 2010a, 2010b, 2013Bañuls Cardona et al, 2012).…”
Section: Maltravieso Cavementioning
confidence: 98%
“…El hueso grabado se recuperó en el nivel A de la Sala de las Chimeneas (Canals et al 2010;Rodríguez-Hidalgo et al 2011), la última cáma-ra de la cueva, de planta sub-circular, sección oval y con una superficie de más de 150 m 2 . El nivel A, que no supera los 20 cm de potencia, se extiende por un área de más de 40 m 2 .…”
Section: Localizaciónunclassified
“…Sus scrofa, Ursus arctos, Vulpes vulpes, Lynx pardinus y Felis silvestris. El estudio zooarqueológico indica una variedad de agentes y procesos tafonómicos implicados en su acumulación: destaca la actividad de pequeños carnívoros (zorro y/o lince) y el uso de la cavidad como lugar de captación y procesamiento de conejos por parte de los humanos (Rodríguez-Hidalgo et al 2011). La malacofauna es escasa: dos conchas perforadas de origen marino (Littorina obtusata y Patella vulgata) utilizadas como elementos de adorno (Rodríguez-Hidalgo et al 2010b) manifiestan la movilidad de los grupos (a la costa hay una distancia de 300 km.)…”
Section: Localizaciónunclassified